Year 6 primary school students’ motivation and perception towards learning English - Tan, Celeste Kir Nie (2023)
English language holds extreme importance especially in today’s modern society. Despite being a second language to many fellow Malaysian, the level of proficiency is still not satisfactory. Therefore, this study aimed to investigate the most common type of motivation, the motivational levels between genders and the students’ perception towards English language activities in Year 6 primary school English as Second Language (ESL) classrooms as they are seen to be the main contributors towards effective language learning. The mixed method whereby online survey questionnaires and interviews was used for this study. The findings showed that the Year 6 students were more intrinsically motivated. Furthermore, unlike intrinsic motivation, only extrinsic motivation was influenced by gender. Although the students’ perception towards ESL activities varied due to personal preferences, the findings showed that students generally gravitated towards interactive and communicative approaches during lessons. This study’s findings beneficially contributes towards tailoring conducive learning activities by educators for successful language learning. Recommendations for future research within this field were proposed.